A liivibrio fischeri L-Asparaginase production by engineered Bacillus subtilis: a potential new biopharmaceutical - Bento, Heitor B. S. [UNESP]; Paiva, Gabriela B. [UNESP]; Almeida, Mafalda R.; Silva, Claúdia G.; Carvalho, Pedro J.; Tavares, Ana P. M.; Pedrolli, Danielle B. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP] (Springer Nature, 2022)
l-Asparaginase (l-ASNase) is an enzyme applied in the treatment of lymphoid malignancies. However, an innovative l-ASNase with high yield and lower side effects than the commercially available preparations are still a market requirement. Here, a new-engineered Bacillus subtilis strain was evaluated for Aliivibrio fischeril-ASNase II production, being the bioprocess development and the enzyme characterization studied. The pBS0E plasmid replicative in Bacillus sp and containing PxylA promoter inducible by xylose and its repressive molecule sequence (XylR) was used for the genetic modification. Initially, cultivations were carried out in orbital shaker, and then the process was scaled up to stirred tank bioreactor (STB). After the bioprocess, the cells were recovered and submitted to ultrasound sonication for cells disruption and intracellular enzyme recovery. The enzymatic extract was characterized to assess its biochemical, kinetic and thermal properties using l-Asparagine and l-Glutamine as substrates. The results indicated the potential enzyme production in STB achieving l-ASNase activity up to 1.539 U mL−1. The enzymatic extract showed an optimum pH of 7.5, high l-Asparagine affinity (Km = 1.2275 mmol L−1) and low l-Glutaminase activity (0.568–0.738 U mL−1). In addition, thermal inactivation was analyzed by two different Kinect models to elucidate inactivation mechanisms, low kinetic thermal inactivation constants for 25 ºC and 37 ºC (0.128 and 0.148 h−1, respectively) indicate an elevated stability. The findings herein show that the produced recombinant l-ASNase has potential to be applied for pharmaceutical purposes.
Keywords: Bacillus subtilis; Enzymatic characterization; Enzymatic thermal inactivation; l-Asparaginase; Stirred tank bioreactor